KOMUNIKASI ANTAR BUDAYA MAHASISWA PERANTAU ASAL GRESIK DALAM MENGHADAPI CULTURE SHOCK DI MADURA - Budi Arif Suyanto; Qoni’ah Nur Wijayani (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to find out how the communication process works, how migrants adapt to the local community in Madura. The method used in this research is a qualitative descriptive method, the data collection technique used is through observation and interviews. The data sources in this research were obtained from interviews with migrant students and also migrant workers/workers. The results of this research showed that when they first migrated to the island of Madura, they felt shocked by the culture practiced by the Madurese people, but as time went by, the migrants felt normal, because they already understood the culture, interaction patterns, and language. carried out by the Madurese people.